Lost in recessions: Youth employment and earnings in Spain - Samuel Bentolila; Florentino Felgueroso; Marcel Jansen; Juan F. Jimeno (SERIEs - Journal of the Spanish Economic Association, 2022)
Young workers in Spain face the unprecedented impact of the Great Recession and the COVID-19 crisis in short sequence. Moreover, they have also experienced a deterioration in their employment and earnings over the last three decades. In this paper, we document this evolution and adopt a longitudinal approach to show that employment and earnings losses suffered by young workers during recessions are not made up in the subsequent expansions. We also estimate the size of the scarring effects of entering the job market in a recession for college-educated workers during their first decade in the labor market. Our empirical estimates indicate that while there is some evidence of scarring effects, the driving force is a trend worsening of youth labor market outcomes.
Keywords: J13; J24; J31; 330; Earnings; Employment; Scarring effects; Youth